A supremacia dos interesses : a manutenção da relação de proximidade e colaboração entre Estado e Igreja Católica durante a República da Espada (1889-1894) - Splendor, Liliane Andréia (2017)
Having as main object of study the relation between the Catholic Church and the republican State during the period comprehended between the years of 1889 and 1894, this work seeks to show how the former, as an institution, positioned itself and acted immediately after the Proclamation of the Republic and throughout the so-called Republic of Sword. Facing the exhibition of the peculiarities of its oscillating, but always active participation in Brazilian society, it seeks to show how the Catholic Church was able, through its discourse and it actions, continue to occupy a prominent position in society and to significantly influence the formation of the new political scenario of the country and the lives of Brazilians citizens. The civilization and the order of the country integrated the project of founding and establishment of the Republic, but because this is a new way of “doing politics” in Brazil, in many moments the rulers felt the need to establish partnerships to facilitate this process. So, it’s possible to defend the argument that the secularism announced by Decree 119-A, which formalized the separation between Church and State, and by the 1891 Constitution, which confirmed the separation and established new terms for the relationship maintained between them, had little or no effectiveness, existing more in theory than in practice. This, in turn, serves to prove that, during the said period, as the title itself already announces, what existed was the maintenance of the cooperation relationship between State and Church and not an autonomus action of both.